Venom proteomics and antivenom neutralization for the Chinese eastern Russell’s viper, Daboia siamensis from Guangxi and Taiwan - Tan, K.Y.; Tan, N.H.; Tan, C.H. (Nature Publishing Group, 2018)
The eastern Russell's viper (Daboia siamensis) causes primarily hemotoxic envenomation. Applying shotgun proteomic approach, the present study unveiled the protein complexity and geographical variation of eastern D. siamensis venoms originated from Guangxi and Taiwan. The snake venoms from the two geographical locales shared comparable expression of major proteins notwithstanding variability in their toxin proteoforms. More than 90% of total venom proteins belong to the toxin families of Kunitz-type serine protease inhibitor, phospholipase A2, C-type lectin/lectin-like protein, serine protease and metalloproteinase. Daboia siamensis Monovalent Antivenom produced in Taiwan (DsMAV-Taiwan) was immunoreactive toward the Guangxi D. siamensis venom, and effectively neutralized the venom lethality at a potency of 1.41 mg venom per ml antivenom. This was corroborated by the antivenom effective neutralization against the venom procoagulant (ED = 0.044 ± 0.002 μl, 2.03 ± 0.12 mg/ml) and hemorrhagic (ED50 = 0.871 ± 0.159 μl, 7.85 ± 3.70 mg/ml) effects. The hetero-specific Chinese pit viper antivenoms i.e. Deinagkistrodon acutus Monovalent Antivenom and Gloydius brevicaudus Monovalent Antivenom showed negligible immunoreactivity and poor neutralization against the Guangxi D. siamensis venom. The findings suggest the need for improving treatment of D. siamensis envenomation in the region through the production and the use of appropriate antivenom.